Antithrombotic properties of pravastatin reducing intra-thrombus fibrin deposition under high shear blood flow conditions - Hamada, Masaaki; Sugimoto, Mitsuhiko; Matsui, Hideto; Mizuno, Tomohiro; Shida, Yasuaki; Doi, Masaaki; Fukushima, Hidetada; Nishio, Kenji; Yoshioka, Akira; Shima, Midori (Thrombosis and Haemostasis, 2011)
In addition to lowering cholesterol, the 3-hydroxyl-3-methylglutaryl coenzyme A reductase inhibitors (statins) have a range of pleiotropic effects that help reduce the risk of adverse cardiovascular events. We sought to understand the molecular mechanisms by which statins could exert anti-platelet actions under physiologic whole blood flow conditions. Using an in vitroperfusion chamber system, we examined the anti-platelet effects of pravastatin under whole blood flow conditions with high or low shear rates. We determined that pravastatin significantly suppressed platelet activation-dependent procoagulant activity, decreasing P-selectin membrane expression, tissue factor accumulation, and thrombin binding within platelet thrombi generated on a von Willebrand factor-surface under high shear rate conditions. These effects resulted in reductions of intra-thrombus fibrin deposition. These antithrombotic properties of pravastatin, which were comparable to those of atorvastatin, could be abrogated by mevalonate. Our experimental approach revealed a novel mechanism mediating the anti-platelet action of statins. Shear rate-dependent antithrombotic activity may explain the favourable effect of pravastatin on the reduction in cardiovascular events that typically occur in vivounder whole blood flow conditions with high shear rates.
Keywords: Statins; high fluid shear; thrombus; von Willebrand factor; fibrinogen/fibrin